Manajemen Evaluasi Pembelajaran PAI Berbasis Aplikasi Liveworksheet di SMP Negeri 3 Lembang - Puspa Anggraini; Bildan Muhammad Sya'ban (Fakultas Tarbiyah dan Keguruan dan UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Technological advancements drive innovation in the management of learning evaluation, including in the field of Islamic Religious Education (PAI). One viable approach is the implementation of digital application-based evaluation, exemplified by the use of Liveworksheet, which supports both the efficiency and effectiveness of the evaluation process. This study aims to describe the management of PAI evaluation based on Liveworksheet in an effort to foster a paperless culture at SMP Negeri 3 Lembang. The research employs a qualitative approach with a case study design, utilizing techniques such as observation, interviews, and documentation to obtain comprehensive data. The findings indicate that evaluation management is conducted through meticulous planning, implementation that is integrated with the learning process, and the use of efficient, environmentally friendly digital evaluation methods. Moreover, the Liveworksheet application not only facilitates teachers in conducting evaluations but also encourages students to become more disciplined, responsible, and environmentally conscious, in alignment with Islamic values.